Usborne first illustrated science dictionary - Khan, Sarah; Whatmore, Candice (Usborne London, 2013)
A brightly illustrated introduction to science which supports teaching in primary schools. Includes a section on 'what is science?' as well information about living things, materials, forces, light, sound and electriciy, space, and scientific investigations